Expectativas de la familia indígena frente a la educación : análisis de caso en la comuna San Miguel del Común, parroquia Calderón. - Terán Moncayo, Alba Johana (2017)
This research presents a sample and analysis of the expectations of indigenous family about education, facing the perception of the community organization, social and family organization. For this was necessary the approach to the educational actors of the “Unidad Educativa Intercultural Bilingüe Mushuk Pakari” of “San Miguel del Comun” commune belonging to the Calderon parish near Quito of the Pichincha province. This research has a qualitative approach, based on a case study, so, it allows to describe and to analyze the posed problem. For the collection of the information was necessary the application of techniques like the participant observation, non-participant observation, and interview. The work is organized in three parts. The first part presents historical and present information of the “San Miguel del Comun”commune of the “Unidad Educativa Intercultural Bilingüe Mushuk Pakari” and the “Kitu Kara” town. In the second part is performed the construction of the theoretical foundation in which is collected the educational process in Ecuador, the categorization of education, indigenous family, interculturality, commune and methodology applied in the field work. Finally, the third part presents the results and analysis of the research.